Investing in Agricultural Productivity in Indonesia (Forum Penelitian Agro Ekonomi, 2016)
EnglishInvestment in agricultural research is a key to agricultural productivity growth. In Indonesia, public investment in agricultural research has expanded significantly in the past two decades, although many agricultural research institutions remain underfunded. The private sector contributes substantially to the financing of public research on plantation crops and forestry. The past decade has also seen a doubling in real terms of agricultural research investment by private companies, although this private investment remains small compared with other developing countries in Asia. Multinational seed, chemical, and animal companies are playing a growing role in transferring new technology to Indonesia. Recent policy shifts have increased private-sector incentives to invest in agricultural research and technology transfer. IndonesianInvestasi dalam riset pertanian adalah kunci bagi peningkatan produktivitas pertanian. Di Indonesia, investasi pemerintah dalam riset pertanian telah berkembang pesat dalam dua dekade terakhir, sekalipun banyak lembaga riset pertanian tetap mengalami kekurangan dana. Sektor swasta memberikan sumbangan yang sangat besar terhadap pembiayaan riset pemerintah dalam bidang tanaman perkebunan dan kehutanan. Dalam dekade terakhir juga telah terjadi perlipatan dua di dalam nilai riil dari investasi dalam riset pertanian yang dilakukan oleh perusahaan-perusahaan swasta, walaupun investasi swasta ini tetap kecil dibandingkan dengan negara-negara berkembang lainnya di Asia. Perusahaan-perusahaan bibit, bahan kimia, dan ternak multunasional memainkan peranan yang semakin besar di dalam transfer teknologi baru ke Indonesia. Perubahan-perubahan kebijakan yang terjadi baru-baru ini telah meningkatkan dorongan bagi sektor swasta untuk melakukan investasi dalam riset pertanian dan transfer teknologi.
Keywords: research investment; technology transfer; government; private sector; agricultural productivity; investasi penelitian; transfer teknologi; pemerintah; swasta; produktivitas pertanian